(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
In an evolving global labor market, durable skills such as communication, adaptability, professionalism, cultural awareness, and customer service are increasingly recognized as essential for success across virtually every industry. Employers consistently report challenges in identifying candidates who can demonstrate these skills, particularly in client-facing fields such as finance and insurance. At the same time, learners often struggle to make their talents and aspirations visible in ways that employers value. This disconnect raises a critical question: How can we open up recognition at the workplace to improve performance and advance careers? Open recognition offers a promising answer. Beyond traditional credentialing, open recognition emphasizes the awareness and appreciation of skills and capabilities in ways that reflect the identities and aspirations of individuals, communities, and workplaces. It provides flexible and inclusive pathways for workers to gain visibility for the durable skills they already possess, while creating opportunities to further develop and demonstrate new ones. This poster presented the story of a unique collaboration among higher education, employers, and open education leaders who came together to design and scale open, competency-based microcredentials in durable skills. Rather than operating in silos, these partners combined expertise in instructional design, openly licensed content, employer-informed assessment, and scalable publishing infrastructure to build a model for recognition that is open, inclusive, and adaptable across contexts. At the heart of this initiative is a suite of 11 open, durable skills microcredentials. Each module is competency-based, freely available, and designed around authentic workplace scenarios. For example, modules on communication, cultural awareness, initiative, technological literacy, and service and sales skills allow learners to demonstrate what they can do in real-world terms. Importantly, the design approach ensures that recognition is not limited to a formal credential. Learners, employers, and communities can adapt these modules to their own needs—applying their own definitions, contexts, and labels while still maintaining core skill integrity. By aligning content with national frameworks while licensing it openly, the project is positioned for broad dissemination and adaptation. Content, faculty training, employer engagement, and integration into workforce programs are in development. These pilots highlight how recognition can function both as a learning tool and as a means for career advancement, supporting performance at work while opening equitable pathways to opportunity. The poster highlighted key insights from this initiative for those interested in advancing open recognition at their own institutions or workplaces. Specifically, it explored: How open recognition can make durable skills visible in ways that matter to both workers and employers. How competency-based, openly licensed microcredentials can support equity by being freely adaptable and accessible. How cross-sector collaboration can sustain inclusive digital credential initiatives and ensure they remain relevant across industries. By engaging with this poster, participants saw how open recognition is more than just issuing a badge or certificate—it is a way to value people’s skills, aspirations, and contributions. They left with practical strategies, sample modules, and a deeper understanding of how “recognition” can drive both workplace performance and career advancement. Keywords: open recognition, durable skills, microcredentials